Diffusion-weighted MRI in the identification of renal parenchymal involvement in children with a first episode of febrile urinary tract infection - Anfigeno, Lorenzo; La Valle, Alberto; Castagnola, Elio; Verrina, Enrico Eugenio; Piaggio, Giorgio; Degl'Innocenti, Maria Ludovica; Piccotti, Emanuela; Wolfler, Andrea; Lembo, Francesca Maria; Bodria, Monica; Formigoni, Clelia; Boetto, Alice; et al. (Frontiers in Radiology, 2024)
This study aims to assess the diagnostic accuracy of diffusion-weighted Magnetic Resonance Imaging (DW-MRI) and determine the inter-reader agreement between two expert radiologists in detecting pyelonephritic foci during the initial episode of febrile urinary tract infection (fUTI) in children aged 0 to 5 years. Also, we aim to establish the correlation between clinical data and DW-MRI findings.Children aged 0 to 5 years presenting with their first episode of fUTI were included in the study and underwent DW-MRI and Ultrasound (US) examinations within 72 hours of admission. Inter-observer agreement between the two expert radiologists in assessing DW-MRI scans was evaluated using Cohen's kappa statistic. Clinical and laboratory data were subjected to statistical analysis.84 children (40 male, 44 female) with a mean age of 7.3 (SD 6.2) months were enrolled. DW-MRI detected pyelonephritis in 78 out of 84 cases (92.9%), with multiple foci observed in 73 out of 78 cases (93.6%). There was a "substantial" level of agreement between the two expert radiologists (κ = 0.725; observed agreement 95.2%).Renal US revealed pyelonephritis in 36 out of 78 cases (46.2%). White blood cell (WBC) count (p = 0.04) and lymphocyte count (p = 0.01) were significantly higher in patients with positive DW-MRI. Although not statistically significant, patients with positive DW-MRI had higher mean values of C-Reactive Protein, Procalcitonin, and neutrophil WBC count (7.72 mg/dL, 4.25 ng/dL, and 9271/μL, respectively).DW-MRI exhibited excellent diagnostic performance in detecting pyelonephritic foci, with substantial inter-reader agreement among expert radiologists, indicating the reliability of the technique. However, a weak correlation was observed between laboratory parameters and DW-MRI results, potentially because of the low rate of negative DW-MRI findings.